ANALISIS PERAN KREDIT MIKRO DARI PD BPR BKK KEBUMEN CABANG KUTOWINANGUN DALAM UPAYA MENGEMBANGKAN USAHA MIKRO DI WILAYAH KERJANYA - Cahyo Trio Utomo; Achma Hendra Setiawan (Universitas Diponegoro, 2013)
Micro, Small and Medium enterprises is the biggest economic actors in Indonesia, which reach 99% of businesses players in Indonesia. In Kebumen Regency on 2009, there were 35,114 micro-businesses managed by entrepreneur, with employment as many as 75,500 workers. In order to increase micro-businesses and developing new entrepreneurs, the government attempts to support the strengthening of the micro-businesses sector. To strengthen the capital, PD BPR BKK Kebumen, as financial institutions which are moving to serve the credits needs of the community in district and village, have distributed a lot of credits to small businesses and medium businesses primarily in the informal and traditional sector. The purpose of this study was to analyze the role of microcredit PD BPR BKK Kebumen Kutowinangun Branch in order to develop micro-businesses in the Kutowinangun District. The variables studied are differences in business capital, production, sales volume and profits before and after receiving credits from PD BPR BKK Kebumen Kutowinangun Branch. The objects of this research were micro-businesses which get credit from PD BPR BKK Kebumen Kutowinangun Branch, in total of 82 micro- business. Types of data collected are primary data and secondary data. The methods of data analysis used were validity test, reliability test, and Wilcoxon sign rank test statistics. Based on the calculations for the Wilcoxon sign rank, the variable capital has increased by 250%. Variable income has increased by 139% after the credit of the PD BPR BKK Kebumen Kutowinangun Branch. For variable profits, has increased by 140% after receiving credits from PD BPR BKK Kebumen Kutowinangun Branch.